Assessment of Mother’s Practice among Using Oral Rehydration Solution for their Children with Diarrhea in Babylon City - Abdulmahdi A. Hasan (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objectives: A descriptive study that aimed to find out demographic characteristics of mothers like age , level of education , occupation and resident area, to find out demographic characteristics of child regarding age , sex and birth order of the child and kind of feeding breast feeding and to assess the mother practices among using oral rehydration solution. Methodology: The study was carried out at Child and Maternal Babylon Hospital, study period extended from December(2016) to end of the February(2017). Anon-probability sample was selected from Child and Maternal Babylon Hospital and al-Hashemia Hospital, the sample consisted (100) mothers. Results : showed that (64% ) of mothers their age between ( 20-30 ) years . also results reveal that ( 56% ) of mothers graduate from primary school ,and show that ( 93% ) of mothers were unemployed.